The Effect of Service Quality on Consumer Satisfaction, Word of Mouth, Brand Trust and Decision to Choose Banking Services at College Employees in the City of Kupang - Koli, Damaris Y.; Sularso, Andi; Sardjono, Sigit (Archives of Business Research, 2019)
The Bank in general aims to support the implementation of national development in order to improve equity, economic growth and national stability towards improving people’s welfare. Banks in Indonesia must carry out their duties and functions properly and are based on the principles of economic democracy. The main functions of commercial banks include collectors, distributors and other bank service providers. The main activities of commercial banks are collecting and channeling funds, while providing other bank services is only supporting activities. Over time, bank services have become increasingly diverse and can be enjoyed by people from various backgrounds such as services and payment transactions or purchases, electricity or telephone account payments through banks. This research aims to examine and analyze effect of service quality on customer satisfaction, word of mouth, brand trust and decision to choose banking services at college employees in the city of Kupang. The population in the study totaled 3.656 bank customers who are college employees in the city of Kupang and the number of samples as much as 360. Technique of data analysis using SEM with SPSS version 20 and AMOS 20. The results of this research it can be concluded that Service quality has a positive and very significant effect on customer satisfaction, Service quality has a positive and significant effect on word of mouth, Service quality has a positive and significant effect on brand trust, Service quality has a positive and insignificant effect on decision to choose, Consumer satisfaction has a positive and significant effect on word of mouth, Consumer satisfaction positive and significant effect on brand trust, Consumer satisfaction has a positive and insignificant effect on decision to choose, Word of mouth has a positive and significant effect on brand trust, Word of mouth has a positive and significant effect on decision to choose and Brand trust positive and significant effect on decision to choose.